Enhancing Photovoltaic Cell Performance Using Heat Sink and Composite Phase - Aouiche wail Kaddouri ali (Université of Eloued, 2025)
The generation of electricity through photovoltaic (PV) systems is among the fastest-growing renewable energy solutions. However, in hot and arid environments, such as the Saharan region, the performance of PV panels is significantly reduced due to heat accumulation, high solar irradiance, and elevated ambient temperatures. To mitigate this thermal degradation, various passive cooling techniques have been explored, including the integration of phase change materials (PCMs). In this study, we numerically evaluate the cooling effect of a Propolis-based natural PCM on the thermal and electrical performance of PV modules. A 2D transient simulation was conducted using ANSYS Fluent, under climatic conditions representative of El-Oued, Algeria. The objective is to improve the energy yield of the PV module by reducing its surface temperature using an eco-friendly thermal regulation layer. Results demonstrated that Propolis effectively lowers the module temperature during peak irradiance and enhances electrical efficiency, confirming its potential as a sustainable alternative to synthetic PCMs. ملخص: من بين أسرع حلول الطاقة )PV( تُعدّ إنتاجية الكهرباء من الأنظمة الكهروضوئية المتجددة نموًا وانتشا اً ر. ومع ذلك، فإن أداء الألواح الشمسية يتأثر سلبًا في المناطق الحارة والجافة مثل المناطق الصح ا روية، وذلك بسبب ت ا ركم الح ا ررة، وشدة الإشعاع الشمسي، وارتفاع درجات الح ا ررة المحيطة. ولمعالجة هذا التدهور الح ا رري، تم استكشاف العديد من تقنيات في هذه الد ا رسة، تم تقييم .)PCM( التبريد السلبي، بما في ذلك دمج المواد متغيرة الطور التأثير التبريدي لمادة متغيرة الطور طبيعية مستخلصة من صمغ النحل )البروبوليس( على الأداء الح ا رري والكهربائي للوحدات الكهروضوئية، وذلك باستخدام محاكاة عددية ثنائية الأبعاد في ظل ظروف مناخية مماثلة لولاية ،ANSYS Fluent غير مستقرة تمت عبر برنامج الوادي – الج ا زئر. ويهدف هذا العمل إلى تحسين إنتاج الطاقة للوحدة الكهروضوئية من خلال تقليل درجة ح ا ررة سطحها باستخدام طبقة تنظيم ح ا رري صديقة للبيئة. وقد أظهرت النتائج أن صمغ النحل يساهم بفعالية في خفض درجة ح ا ررة الوحدة خلال ساعات الذروة الشمسية، مما يؤدي إلى تحسين الكفاءة الكهربائية، ويؤكد إمكاناته كبديل مستدام للمواد الصناعية متغيرة الطور.
Master's theses: specializing in Mechanical Renewable Energy.2025
Keywords: Photovoltaic panels; passive cooling; Propolis; phase change material; CFD simulation; Saharan climate; الألواح الكهروضوئية، التبريد السلبي، صمغ النحل، المواد متغيرة الطور، المحاكاة العددية، المناخ الصح ا روي.